2014
DOI: 10.1039/c3cc45518a
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing mechanistic labyrinths in gold(i) catalysis

Abstract: Gold(i) controls complex transformations proceeding through carbocationic species by stabilising the key reactive intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(115 citation statements)
references
References 244 publications
1
112
0
Order By: Relevance
“…[21][22][23][24][25][26] We have chosen 1-phenylpropyne as a model alkyne and [AuCl(PPh 3 )] and [AuCl(IPr)] (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) as representative catalysts. It has been shown that with a gold catalyst bearing a small ligand such as trimethylphosphine or triphenylphospine the reaction proceeds via the formation of geminally diaurated complexes, which are subsequently protodeaurated to form the product of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26] We have chosen 1-phenylpropyne as a model alkyne and [AuCl(PPh 3 )] and [AuCl(IPr)] (IPr = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene) as representative catalysts. It has been shown that with a gold catalyst bearing a small ligand such as trimethylphosphine or triphenylphospine the reaction proceeds via the formation of geminally diaurated complexes, which are subsequently protodeaurated to form the product of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…6 According to the generally accepted mechanism for gold-catalyzed functionalization of unsaturated hydrocarbon compounds (UHC), the first step consists of the coordination of the gold fragment [LAu] + to the UHC. Upon coordination, the substrate becomes electronically depleted and prone to undergo a nucleophilic attack.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We hypothesized that the low reactivity of 8a was due to its lower electron density and greater steric hindrance of the alkyne, compared to the alkyne in 5 . Therefore, we evaluated catalysts with higher electrophilicity, [37] as well as platinum catalysts, which have been utilized in efficient carbocyclizations of 1,6-enynes. [38, 39] However in our system, the majority of the substrate decomposed with all platinum catalysts tested (entries 3-5).…”
Section: Resultsmentioning
confidence: 99%
“…It was also suggested that aurophillic bonded intermediates were involved in gold-catalyzed transformations. [37,41] These may lead to undesired reaction pathways, resulting in low yield of the desired product. [40] Hence, we decided to screen additional phosphine ligands.…”
Section: Resultsmentioning
confidence: 99%